Immune electron microscopy of avian infectious bronchitis virus serotypes. - Odenwald, W F (1978)
An immune electron microscopy agglutination technique in which emphasis is placed upon the importance of antigen-antibody equivalence has been developed as a possible method for the serotyping of avian infectious bronchitis viruses. The Connecticut and Massachusetts 41 serotypes were used as a model system. Stock virus concentrations were standardized by physical particle counts of virions sedimented directly onto electron microscope specimen grids. Suspensions containing approximately 150 virions per grid square were allowed to react with dilutions of homologous and heterologous antisera. Virions in these constant virus-variable serum mixtures were sedimented directly onto electron microscope specimen grids, and the relative degree of aggregation per grid was determined from the mean percent aggregation of five randomly selected grid squares. In homologous assays, regions of relative antibody excess, of equivalence, and of relative antigen excess were clearly evident. At equivalence, the mean percent aggregation was significantly higher than in the regions of relative antibody or antigen excess. In the heterologous systems, the degree of aggregation differed little from that of the virus controls containing no antiserum.